Analisis Kepuasan Kerja Karyawan Kontrak Perum Peruri Karawang - Taufiq Romadon; Nandang Nandang; Zenita Apriani (Universitas Batanghari, 2023)
This study aims to analyze the job satisfaction of contract employees at Perum Peruri Karawang. This study involved contract employees from various work units. Research using descriptive qualitative research. There are five dimensions of Afandi's theory which are the focus of research, namely the dimensions of Work, Wages/Salary, Promotion, Colleagues, Supervision. The collection technique was carried out through three stages, namely observation, interviews and documentation. The results showed that contract employees were satisfied with the work indicators, salary indicators, supervisor indicators, and co-workers indicators. However, employees are dissatisfied with the promotion indicators, because the company has not given contract employees another chance to become permanent employees at Perum Peruri for the last five years or so. For promotion indicators, it is suggested that the company make regulations for the period of time for the transfer of work status that are clearly applicable in the company.